Jurisdiction, Rule of Law, and Unity of EU Law in Rosneft - Mirka Kuisma (Oxford University Press, 2022)
This article engages in a critical reading of the treatment of issues concerning the jurisdiction of the European Court of Justice (the Court), the rule of law, and the principle of unity of Union law in the Rosneft ruling of March 2017, and offers a contemplation of the nature of the Court’s jurisdiction and of its role in the Union legal order. In Rosneft, the Court engaged in a judicial correction of the scheme of CFSP remedies in the Treaties. In light of previous developments in case-law, the finding of jurisdiction to hear preliminary rulings on the validity of CFSP acts in Rosneft was doctrinally unsurprising. That being said, the justifications offered for that finding in the ruling slightly mistreat both the Treaty text and the case-law upon which they build. The reading given to Rosneft in this article suggests that the outcome of the jurisdictional question in the case is centrally based on considerations flowing from the principle of unity of Union law and the Foto-Frost maxim. This notwithstanding, the Court’s reasoning rested centrally on argumentation on the basis of the principle of rule of law, thus making the justifications seem like a veneer rather than a transparent representation of the logic underlying the ruling. It is suggested that in light of the interests at play, a more open emphasis of all relevant considerations in the ruling would have been both possible and preferable. After sketching an alternative reasoning for the rationale of Rosneft and discussing the risk of future expansion of Article 267 TFEU jurisdiction within the field of CFSP, the article concludes by drawing conclusions on the implications of the chosen manner of justification for the Court itself, and on the importance of the Court’s self-depiction in Rosneft for the broader scheme of the Treaties.